A highly immunogenic vaccine against A/H7N9 influenza virus. Issue 6 (3rd February 2016) - Cao, Weiping; Liepkalns, Justine S.; Hassan, Ahmed O.; Kamal, Ram P.; Hofstetter, Amelia R.; Amoah, Samuel; Kim, Jin Hyang; Reber, Adrian J.; Stevens, James; Katz, Jacqueline M.; Gangappa, Shivaprakash; York, Ian A.; et al.
Abstract: Since the first case of human infection in March 2013, continued reports of H7N9 cases highlight a potential pandemic threat. Highly immunogenic vaccines to this virus are urgently needed to protect vulnerable populations who lack protective immunity. In this study, an egg- and adjuvant-independent adenoviral vector-based, hemagglutinin H7 subtype influenza vaccine (HAd-H7HA) demonstrated enhanced cell-mediated immunity as well as serum antibody responses in a mouse model. Most importantly, this vaccine provided complete protection against homologous A/H7N9 viral challenge suggesting its potential utility as a pandemic vaccine.